Pulmonary arteriovenous malformations after the superior cavopulmonary shunt: mechanisms and clinical implications. (June 2014) - Kavarana, Minoo N; Jones, Jeffrey A; Stroud, Robert E; Bradley, Scott M; Ikonomidis, John S; Mukherjee, Rupak
<x xml:space="preserve">Abstract</x> Children with functional single ventricle heart disease are commonly palliated down a staged clinical pathway toward a Fontan completion procedure (total cavopulmonary connection). The Fontan physiology is fraught with long-term complications associated with lower body systemic venous hypertension, eventually resulting in significant morbidity and mortality. The bidirectional Glenn shunt or superior cavopulmonary connection (SCPC) is commonly the transitional stage in single ventricle surgical management and provides excellent palliation. Some studies have demonstrated lower morbidity and mortality with the SCPC when compared with the Fontan. Unfortunately the durability of the SCPC is significantly limited by the development of pulmonary arteriovenous malformations (PAVMs) which have been commonly attributed to the absence of hepatic venous blood flow and the lack of pulsatile flow to the affected lungs. Abnormal angiogenesis has been suggested as a final common pathway to PAVM development. Understanding these fundamental mechanisms through the investigation of angiogenic pathways associated with the pathogenesis of PAVMs would help to develop medical therapies that could prevent or reverse this complication following SCPC. Such therapies could improve the longevity of the SCPC, potentially eliminate or significantly postpone the Fontan completion with its associated complications, and improve long-term survival in children with single ventricle disease.